Pengaruh Kepercayaan Produk dan Nilai Pelayanan Terhadap Niat Beli Melalui Preferensi Merk dari Ponsel - Putri, Alya Natalie; Almuzzaky, Muhammad Irham; Saajid, Muhammad Musyaffa (Applied Business and Administration Journal, 2023)
Companies in innovating a product aim because of the increasingly intense competition in the world of industry 5.0 era so that by testing brand trust, brand preference, perceived value and purchase intention it is expected to be a factor in the success of a company. The research conducted by the author uses hypothesis testing and is classified as cross-sectional, namely by using a respondent's quiz using the Google form. This study found findings that brand trust did not have a positive impact on purchase intention, while brand trust had a good impact on brand references, and perceived value had a positive effect on purchase intention and lastly, perceived value had an effect on brand preference.